Applications of polymerase chain reaction for identification of dengue viruses isolated from patient sera - Maneekarn N. (2014)
A simple and sensitive procedure of reverse transcriptase polymerase chain reaction (RT-PCR) was developed previously such that all 4 serotypes of dengue viruses could be detected and their serotypes identified simultaneously in a single-step procedure. In this study we compared the RT-PCR with a conventional immunoperoxidase (PAP) staining method for the identification of dengue viruses currently isolated from patient sera. Sixty-six sera taken from dengue hemorrhagic fever (DHF) patients were subjected to virus isolation by inoculating onto C6/36 cell cultures. Screening for the presence of dengue viruses in culture fluids was done after 7 days of incubation by PAP staining using hyperimmune rabbit anti-dengue virus antibody as the primary reagent. Dengue viruses in positive cultures were further identified for their serotypes by PAP using type-specific monoclonal antibodies (MAb) and by RT-PCR. Thirty-two out of the 66 serum specimens tested (48.5%) were positive for dengue viruses. Of these, 5 were type 1 (DEN-1), 25 were type 2 (DEN-2) and 2 contained both DEN-1 and DEN-2. All cultures that were positive by PAP method were also positive by RT-PCR and vice versa. Thus, the results obtained by RT-PCR were in good agreement with those by PAP. It is important to point out that while all 5 DEN-1 isolates reacted readily with the MAb 1F1, only 2 of them could be identified by the MAb 15F3. Our data suggest that antigenic variation among DEN-1 isolates occur frequently and this should be taken into consideration in the selection of appropriate type-specific MAb for serotyping of dengue viruses.(ABSTRACT TRUNCATED AT 250 WORDS)